Outbreak of acute gastroenteritis associated with drinking water in rural Kazakhstan: A matched case-control study - Madina Orysbayeva; Balaussa Zhuman; Dinara Turegeldiyeva; Roberta Horth; Bakhytkul Zhakipbayeva; Daniel Singer; Manar Smagul; Dilyara Nabirova (Public Library of Science (PLoS), 2022)
We conducted an outbreak investigation from June 3 to 15th in a rural village in northern Kazakhstan, after surveillance showed an increase in gastroenteritis. Cases were residents who presented for medical treatment for diarrhea, fever (>37.5 °C), vomiting, or weakness from May 14 to June 15, 2021. Controls were residents matched by age ±2 years at a ratio of two controls for every case. Cases and controls were interviewed using structured questionnaires. We abstracted clinical data from medical records. We mapped cases and assessed risk for disease using conditional multivariable logistic regression. We identified 154 cases of acute gastroenteritis (attack rate of ~26 per 1,000 inhabitants). Symptoms were diarrhea, fever, vomiting, weakness, and decreased appetite. Among cases that participated (n = 107), 74% reported having drank unboiled tap water vs 18% of controls (n = 219). This was the only risk factor associated with disease (adjusted odds ratio: 18; 95% CI 9-35). Drinking water from a dispenser or carbonated drinks was protective. The city has two water supply networks; cases were clustered (107 cases in 79 households) in one. The investigation found that monitoring of quality and safety of water according to national regulations had not been conducted since 2018. No fatalities occurred, and no associated cases were reported after our investigation. Results suggest that untreated tap water was the probable source of the outbreak. The water supply had been cleaned and disinfected twice by the facility 2 days before our investigation began. Recommendations were made for regular monitoring of water supply facilities with rapid public notification when issues are detected to reduce likelihood of future drinking water associated outbreaks.